Motivational strategies for improving the academic performance of accounting and auditing students at the University of Chimborazo Ecuador 2015 - Montalvo Larriva, Guillermo Eduardo (2019)
Scientific research we have done is basic, is quasi-experimental factors are twofold: program of motivational strategies and academic performance of students studying accounting and auditing at the University of Chimborazo Ecuador 2015. The population is made up 324 undergraduates accounting and auditing at the University of Chimborazo and the sample consists of 60 students for the control group and 60 for the experimental group, which in total represent combined total of 120 students The research design is transactional, quasi-experimental, bivariate, cross. For data collection 15 workshops on a program of motivational strategies and a questionnaire for motivational strategies that applied to students of the sample was performed. The instruments meet the qualities of validity and reliability. The study raises the following hypothesis: There is significant difference between the control group and the experimental group in post test after implementing the program of motivational strategies "EMODECA" in the academic performance of students studying accounting and audit at the University of Chimborazo Ecuador 2015. The results allow us to refuse to accept the investigation, as in the control group the hypothesis p- value is less than 0.05, therefore no significant improvement in the experimental group and the p- value with a level of significance of 95% reliability is 0.00 according to the nonparametric Mann - Whitney, therefore the null hypothesis is rejected and therefore the investigated hypothesis is accepted and we have: There is a difference between the group control and experimental group in post test after implementing the program of motivational strategies "EMODECA" in the academic performance of students studying accounting and auditing at the University of Chimborazo Ecuador 2015.